2023
DOI: 10.1186/s12974-022-02688-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from mesenchymal stem cells reduce neuroinflammation in hippocampus and restore cognitive function in hyperammonemic rats

Abstract: Chronic hyperammonemia, a main contributor to hepatic encephalopathy (HE), leads to neuroinflammation which alters neurotransmission leading to cognitive impairment. There are no specific treatments for the neurological alterations in HE. Extracellular vesicles (EVs) from mesenchymal stem cells (MSCs) reduce neuroinflammation in some pathological conditions. The aims were to assess if treatment of hyperammonemic rats with EVs from MSCs restores cognitive function and analyze the underlying mechanisms. EVs inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…As reported in various studies, bMSC‐EVs have recently been shown to improve cardiac function, promote neo‐angiogenesis both in vitro and in vivo, improve cardiac indices, reduce infarct size, and regulate homeostasis in various rodent models of myocardial infarction (MI) (Kore et al., 2021, Sun et al., 2020, Yao et al., 2021, Zheng et al., 2022). Additionally, MSC‐EVs have been reported to regulate neuroinflammation, neurogenesis (Izquierdo‐Altarejos et al., 2023), repair ischemic stroke (Davis et al., 2021), and improve neurological function in various animal models of traumatic brain injury (TBI) (Amini et al., 2023), Parkinson's disease (PD), and Alzheimer's disease (AD) (Reed & Escayg, 2021). MSC‐EVs can deliver long noncoding RNA (lncRNA) KLF3‐AS1, which promotes SIRT1 deubiquitination, reduces cerebral infarction, and improves neurological function in a mouse model (Xie et al., 2023).…”
Section: Types Of Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…As reported in various studies, bMSC‐EVs have recently been shown to improve cardiac function, promote neo‐angiogenesis both in vitro and in vivo, improve cardiac indices, reduce infarct size, and regulate homeostasis in various rodent models of myocardial infarction (MI) (Kore et al., 2021, Sun et al., 2020, Yao et al., 2021, Zheng et al., 2022). Additionally, MSC‐EVs have been reported to regulate neuroinflammation, neurogenesis (Izquierdo‐Altarejos et al., 2023), repair ischemic stroke (Davis et al., 2021), and improve neurological function in various animal models of traumatic brain injury (TBI) (Amini et al., 2023), Parkinson's disease (PD), and Alzheimer's disease (AD) (Reed & Escayg, 2021). MSC‐EVs can deliver long noncoding RNA (lncRNA) KLF3‐AS1, which promotes SIRT1 deubiquitination, reduces cerebral infarction, and improves neurological function in a mouse model (Xie et al., 2023).…”
Section: Types Of Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…This theory is further encouraged by P2X7 antagonists that inhibit the P2X7-NLRP3-IL-1β pathway [ 168 ]. The extracellular vesicles of MSCs, as described above, are already known to reduce neuroinflammation—one of the key factors implicated in the etiology of mood disorders [ 169 ].…”
Section: Role Of Purinergic Signaling In Asd and Comorbiditiesmentioning
confidence: 99%
“…These findings were partially consistent with previous studies (Kong et al., 2016, 2021; Luo et al., 2018). Basal ganglia had been proved to be related with brain function and structure in HE (Zhang et al., 2013), and hippocampus was related with cognitive functions including learning and memory (Izquierdo‐Altarejos et al., 2023). Both RIF and LAC proved effective for improving motor ability and reducing neuroinflammation in BDL rats.…”
Section: Disscussionmentioning
confidence: 99%